Application of digital surgical guides in mandibular resection and reconstruction with fibula flaps. Issue 11 (November 2016) - Yuan, X.; Xuan, M.; Tian, W.; Long, J.
Abstract: Surgical guides have been used widely in maxillofacial surgery. Details of the types of digital surgical guide used in mandibular resection and reconstruction with fibula flaps at the authors' institution are presented in this article. Three patients diagnosed with mandibular ameloblastoma underwent mandibular resection and reconstruction with fibula flaps using surgical guides for assistance. These digital surgical guides included a mandibular osteotomy guide, a fibular osteotomy guide, and a mandibular fixation guide. Surgical guides are helpful in improving the accuracy of operations and are appropriate for many types of mandibular resection and reconstruction.